U POTRAZI ZA PRIPADANJEM U EVROPI KOJA SE MIJENJA - Hodžić, Dželaludin (Novi Muallim, 2010)
Prikaz knjige: (“Identity - The search for belonging in a Changing Europe”, ur. M. Tanner, Balkan Fellowship for Journalistic Excellence, Sarajevo, 2009. godine)